DOES PRETERM INFANTS BORN OUTSIDE TERTIARY PERINATAL CENTRE HAVE AN IMPACT ON NEURODEVELOPMENTAL AND GROWTH OUTCOME AT 36 MONTHS CORRECTED AGE?. (18th May 2018) - Soraisham, Amuchou; Sheta, Ayman; Ringtham, Catherine; Tang, Selphee; Creighton, Diane; Hendson, Leonora; Lodha, Abhay
Abstract: BACKGROUND: Infants born in tertiary perinatal centres (inborn) have higher survival and lower morbidity than outborn infants. However, there is limited information regarding the long term neurodevelopmental and growth outcomes among outborn preterm infants. OBJECTIVES: To compare the neurodevelopmental and growth outcomes at 36 months corrected age (CA) between outborn and inborn infants born < 29 weeks. DESIGN/METHODS: This is a retrospective cohort study. We included infants born <29 weeks admitted to Foothills Medical Centre, Calgary between January 2000 and December 2012, who had neurodevelopmental(ND) assessment up to 36 months CA. Infants with intrauterine infection, major congenital and chromosomal anomalies were excluded. Our primary outcome was composite of death or neurodevelopmental impairment (NDI). We compared ND and growth outcomes between inborn and the outborn infants using univariate and multivariate logistic regression analysis. RESULTS: Of 1235 eligible infants, 175 (14%) were outborn. Outborn infants were lower in GA (25.8 ± 1.7 wk vs 26.2 ± 1.5 wk), had lower chorioamnionitis rate (15% vs 24%), received less antenatal steroid (55% vs 90%) and maternal antibiotics (51% vs 68%). Neonatal morbidities were similar between the two groups except that outborn infants had higher rates of severe brain injury (24% vs 12%) and mortality (22% vs 11%). Of 1078 eligible survivors, 1048 (97%) were followed. There was no difference in ND outcomes (Table). Multivariate regression analysis controlling for potential confounders (GA, gender, chorioamnionitis, antenatal steroids and maternal age) showed outborn status was not associated with composite primary outcome of death or ND impairment (adjusted OR: 1.09, 95% CI, 0.69, 1.70). Growth outcomes were not significantly different between two groups. CONCLUSION: In this cohort, neurodevelopmental and growth outcomes does not appear to be significantly different between outborn and infants at 36 months corrected age.